Higher Order Thinking Skills: How Preservice MathematicsTeachers perceive? (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
The main objective of this study was to explore mathematics teachers’ perception on Higher Order Thinking Skills (HOTS). The explanatory sequential mixed method with Likert scale and interview guideline was used as research tools for data collection. 50 mathematics teachers who were teaching at Higher Education were conveniently selected for the survey and 5 of them were interviewed. The mean and standard deviation of different views on Likert scale were calculated and the results from quantitative data are presented in language with the help of qualitative data obtained from the interview. The teachers' perception was gathered about concept or understanding, needs, clarity, and practice about the HOTS. The study found that most of the teachers viewed HOTS as a commonly known idea of analyzing and synthesizing skills together with logical thinking and decision making skills. In depth, teachers were clear about the meanings, strategies and the use of HOTS but weak in implementation. Majority of the teachers viewed the practice of HOTS in mathematics classrooms as necessary but they were rarely used. Only a few of them were partially practicing them in classroom instruction. The teachers felt complexity in practicing HOTS due to students’ basic knowledge, approach and access to different materials, teachers’ training, curriculum and time of implementation in development of HOTS in students. यस अध्ययनको मुख्य उद्देश्य हायर अर्डर थिंकिङ स्किल (HOTS) मा गणित शिक्षकहरूको धारणा अन्वेषण गर्नु थियो। लाइकर्ट स्केल रअन्तर्वार्ता दिशानिर्देशको साथ व्याख्यात्मक अनुक्रमिक मिश्रित विधि डेटा संग्रहको लागि अनुसन्धान उपकरणको रूपमा प्रयोग गरिएको थियो।उच्च शिक्षामा पढाउने ५० गणित शिक्षकलाई सहज रूपमा सर्वेक्षणका लागि छनोट गरिएको थियो र तीमध्ये ५ जनाको अन्तर्वार्ता लिइएको थियो। लाइकर्ट स्केलमा विभिन्न विचारहरूको औसत र मानक विचलन गणना गरियो र अन्तर्वार्ताबाट प्राप्त गुणात्मक तथ्याङ्कको सहायतालेमात्रात्मक तथ्याङ्कबाट प्राप्त नतिजाहरूलाई भाषामा प्रस्तुत गरिन्छ। HOTS बारे अवधारणा वा बुझाइ, आवश्यकता, स्पष्टता र अभ्यासकोबारेमा शिक्षकहरूको धारणा जम्मा गरिएको थियो। अध्ययनले पत्ता लगायो कि धेरै जसो शिक्षकहरूले HOTS लाई तार्किक सोच र निर्णय गर्नेसीपहरू सँगै विश्लेषण र संश्लेषण गर्ने सामान्य रूपमा ज्ञात विचारको रूपमा हेरे। गहिराइमा, शिक्षकहरू HOTS को अर्थ, रणनीति र प्रयोगकोबारेमा स्पष्ट थिए तर कार्यान्वयनमा कमजोर थिए। धेरैजसो शिक्षकहरूले गणित कक्षाकोठामा HOTS को अभ्यासलाई आवश्यक ठान्थे तरतिनीहरू विरलै प्रयोग भएका थिए। तिनीहरूमध्ये केहीले मात्र कक्षाकोठा निर्देशनमा आंशिक रूपमा अभ्यास गरिरहेका थिए। विद्यार्थीहरूकोआधारभूत ज्ञान, दृष्टिकोण र विभिन्न सामग्रीहरूमा पहुँच, शिक्षकहरूको तालिम, पाठ्यक्रम र विद्यार्थीहरूमा HOTS विकासको लागिकार्यान्वयनको समयका कारण शिक्षकहरूले HOTS अभ्यास गर्न जटिलता महसुस गरे।